Melatonin seed priming improves early establishment and water stress tolerance of peanut - de Camargo Santos, Aline; Schaffer, Bruce; Ioannou, Andreas G.; Moon, Pamela; Shahid, Muhammad; Rowland, Diane; Tillman, Barry; Bremgartner, Matthew; Fotopoulos, Vasileios; Bassil, Elias (My University, 2024)
Water stress is a major cause of yield loss in peanut cultivation. Melatonin seed priming has been used to enhance stress tolerance in several crops, but not in peanut. We investigated the impact of seed priming with melatonin on the growth, development, and drought tolerance of two peanut cultivars, TUFRunner™ '511', a drought tolerant cultivar, and New Mexico Valencia A, a drought sensitive cultivar. Peanut seed priming tests using variable rates of melatonin (0-200 μM), indicated that 50 μM of melatonin resulted in more uniform seed germination and improved seedling growth in both cultivars under non stress conditions. Seed priming with melatonin also promoted vegetative growth, as evidenced by higher whole-plant transpiration, net CO2 assimilation, and root water uptake under both well-watered and water stress conditions in both cultivars. Higher antioxidant activity and protective osmolyte accumulation, lower reactive oxygen species accumulation and membrane damage were observed in primed compared with non-primed plants. Seed priming with melatonin induced a growth promoting effect that was more evident under well-watered conditions for TUFRunnner™ '511', whereas for New Mexico Valencia A, major differences in physiological responses were observed under water stress conditions. New Mexico Valencia A primed plants exhibited a more sensitized stress response, with faster down-regulation of photosynthesis and transpiration compared with non-primed plants. The results demonstrate that melatonin seed priming has significant potential to improve early establishment and promote growth of peanut under optimal conditions, while also improve stress tolerance during water stress.
Keywords: Crop resilience; Melatonin; Peanut; Phenotyping; Seed priming; Stress acclimation; Water stress